Strengthening social cohesion: the impact of SAP schools on cultural awareness and multiracial unity - Erni Ezzanie Binte Abdol Hamid (Nanyang Technological University, 2024)
Despite much conversation regarding its purpose, Chinese-medium Special Assistance Plan (SAP) schools still maintain their presence within Singapore’s education system. Singapore has often promoted itself globally as a multicultural society and many policies take into consideration the different cultural groups recognised in the country. Additionally, many scholars have identified schools to be one of the essential institutions that play a pivotal role in shaping and influencing the perception of students through social interactions with their peers. Thus, there is a contradiction between the existence of SAP schools and their roles in enriching students’ knowledge of the other cultural groups in Singapore. This research paper examines the influence of Special Assistance Plan (SAP) schools in Singapore on students’ awareness and understanding of the diverse cultures present in multiracial Singapore.